2015
DOI: 10.12738/estp.2015.4.2434
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Relationship between Self-Handicapping Tendencies, Self-Esteem and Cognitive Distortions

Abstract: The purpose of this study is to examine the relationship between cognitive distortions, self-handicapping tendencies, and self-esteem in a sample of students studying in a school of education. The sample of the study was comprised of 507 volunteer students chosen through random sampling from a total of 4,720 students who were studying teaching at Nigde University and Aksaray University, located in central Anatolia in Turkey. The self-handicapping scale, cognitive distortions scale, and Rosenberg self-esteem sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 39 publications
0
15
0
4
Order By: Relevance
“…The results of Cooley and Pedersen (19) demonstrated that people with low selfesteem, who experienced unexpected failures, indicated high levels of dysfunction such as self-handicapping. The results of another study carried out by Yavuzer (20) showed that cognitive distortions (self-criticism, self-blame, hopelessness, and preoccupation with danger) and self-esteem were significant predictors of self-handicapping tendencies.…”
Section: Discussionmentioning
confidence: 94%
“…The results of Cooley and Pedersen (19) demonstrated that people with low selfesteem, who experienced unexpected failures, indicated high levels of dysfunction such as self-handicapping. The results of another study carried out by Yavuzer (20) showed that cognitive distortions (self-criticism, self-blame, hopelessness, and preoccupation with danger) and self-esteem were significant predictors of self-handicapping tendencies.…”
Section: Discussionmentioning
confidence: 94%
“…In the study, it was articulated that the self-handicapping levels of the female prospective teachers were higher than the male prospective teachers. The related literature shows that the self-handicapping level of women is higher than that of men and verbal self-handicapping types is more common among women (Yavuzer, 2015;McCrea et al, 2007;Kolditz and Arkin, 1982;Shepperd and Arkin, 1989). In the study conducted by Kaya et al on prospective teachers it was found that that self-handicapping levels of female prospective teachers were higher than male prospective teacher (Kaya, et al, 2017).…”
Section: Discussion and Suggestionsmentioning
confidence: 99%
“…Perhaps others demonstrate thoughts that fall outside these themes altogether. For example, it is entirely possible that a person might demonstrate cognitive distortions related to self-esteem (e.g., “I am not capable of overcoming this problem”) that equate to self-handicapping during treatment (see Yavuzer, 2015). We suggest that careful and consistent thought monitoring (using a log that is modified for this purpose), perhaps over an extended period of time, is the best way to discern the pattern or theme that will be the ultimate target of restructuring for a given client.…”
Section: Recommendations To Clinicians and Studentsmentioning
confidence: 99%